Edible mushroom (Flammulina velutipes) as biosource for silver nanoparticles: from synthesis to diverse biomedical and environmental applications. (18th November 2020) - Faisal, Shah; Khan, Muhammad Aslam; Jan, Hasnain; Shah, Sajjad Ali; Abdullah,; Shah, Sumaira; Rizwan, Muhammad; Ullah, Wajid; Akbar, Muhammad Taj; Redaina,
Abstract: The current study reports advanced, ecofriendly and biosynthesized silver NPs for diverse biomedical and environmental applications using Flammulina velutipes as biosource. In the study, a simple aqueous extract of F. velutipes was utilized to reduce the AgNO3 into stable elemental silver (Ag 0 ) at a nanometric scale. The NPs had average size of 21.4 nm, spherical morphology, and were highly stable and pure. The characterized nanoparticles were exploited for a broad range of biomedical applications including bacteriocidal, fungicidal, leishmanicidal, in vitro antialzheimer's, antioxidant, anti-diabetic and biocompatibility studies. Our findings showed that F. velutipes mediated AgNPs exhibited high activity against MDR bacterial strains and spore forming fungal strains. All the tested urinary tract infection bacterial isolates, were resistant to non-coated antibiotics but by applying 1% of the synthesized AgNPs, the bactericidal potential of the tested antibiotics enhanced manifolds. The NPs also exhibited dose-dependent cytotoxic potential against Leishmania tropica with significant LC50 of 248 μ g ml −1 for promastigote and 251 μ g ml −1 for amastigote forms of the parasite. Furthermore, promising antialzheimer and antidiabetic activities were observed as significant inhibition of α -amylase, α -glucosidase, acetylcholinesterase (AChE) and butrylcholineterase (BChE) were noted. Moreover, remarkable biocompatible nature of the particles was found against human red blood cells. The biosynthesized AgNPs as photocatalyst, also resulted in 98.2% degradation of indigo carmine dye within 140 min. Owing to ecofriendly synthesis, biosafe nature and excellent physicochemical properties F. velutipes AgNPs can be exploited as novel candidates for multifaceted biomedical and environmental applications.